The Abuse of Freedom of Speech in the Digital Era: Social Media in the Perspective of Constitutional Law - Ridwan Syaidi Tarigan; Antonius Felix (Journal of Law, Politic and Humanities, 2026)
Freedom of expression in digital spaces confronts increasingly complex constitutional challenges as social media becomes the dominant arena of contemporary public discourse. This study examines the abuse of expressive freedom on social media through a constitutional law framework, integrating normative-doctrinal analysis with multistakeholder empirical inquiry. The primary theoretical contribution lies in the construction of a constitutionally grounded analytical framework that evaluates digital speech regulation against the principles of lex certa, proportionality, and legal certainty as mandated by the 1945 Indonesian Constitution. The study engaged 25 purposively selected respondents across four strategic groups social media users, law enforcement officials, legal practitioners, and constitutional law academics to ensure normative depth alongside implementation insight. Findings reveal a constitutionally significant gap between the expressive freedom guarantees under Article 28E and the operational realities of ITE Law enforcement. The statute demonstrably produces structural chilling effects that suppress constitutionally protected expression, violates the proportionality standard embedded in Article 28J, and fails the lex certa threshold due to its high degree of normative ambiguity. This study argues that meaningful digital regulatory reform demands not merely technical revision but a paradigmatic reorientation that repositions freedom of expression as a primary constitutional value rather than a residual concession. A hybrid governance model integrating regulatory oversight with community-based moderation mechanisms, anchored within a coherent constitutional framework, is proposed as a principled and sustainable solution.